DEVELOPING POSITIVE CHARACTER: PSYCHOLOGICAL STRATEGIES FOR PERSONAL GROWTH - Ghadiza Chalil Tjan; Siti Munadiyah; Mu’mina Kurniawati S.J. Kahar; Abdul Halil Hi. Ibrahim (International Journal of Teaching and Learning, 2025)
Developing positive character is an important aspect in shaping an individual's personality and morals, which is effectively done through the application of holistic and sustainable psychological strategies. These strategies include instilling moral values, setting an example, providing positive reinforcement, and developing social and emotional skills in accordance with the child's stage of development. In addition, the environment and education system play a major role in supporting this process, where a conducive, safe, and appreciative atmosphere can strengthen the internalisation of positive values. In the context of education, the implementation of a character-based curriculum integrated with psychological approaches such as cooperative learning, value-based learning models, and reinforcement through digital media and technology, has proven effective in improving the positive attitudes and behaviour of students. Research findings show that this strategy not only improves moral and social aspects but also strengthens a sense of responsibility, honesty, and empathy. Therefore, synergy between a supportive environment and an innovative education system is key to producing a generation with strong character and high integrity, capable of facing social dynamics and the challenges of the times.